SOLVATION FREE ENERY OF THIENO [3, 2 - b] PYRIMIDINE ANALOGS COMPRISING INTERMOLECULAR SOLVATION AND INTRAMOLECULAR SELF-SOLVATION - K, Prabhu; Mahto, Manoj Kumar; VK, GOPALAKRISHNAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: The aim was to estimate the various physiochemical properties of a molecule and the de-solvation cost for its binding to macromolecular receptors, the solvation free energy is a fundamental thermodynamics that has to be used. Here, a new solvation free energy carried out through the improvement of the existing solute-solvent interaction model and test its applicability in estimating the solvation free energies of vascular endothelial growth factor receptor-2 (VEGFR-2) inhibitors are discussed. Methods: The molecular dynamics program GROMACS, which is designed for free energy calculations and bond simulations, has been used to understand the solvation free energies. Results: The estimates of the solvation free energies of VEGFR-2 inhibitor molecules showed a reasonable accuracy by combining the effects from the solvent exposed and self-solvation regions. This significant contribution of free energies is thus consistent with the stability of the inhibitors in the solvent. Conclusion: The estimated solvation free energies from the new model illustrated a good association with the solute-solvent interaction. The current solvation model is thus expected to be more useful in supporting the stability of the inhibitors within a solvent. Keywords: GROMACS, Solvation free energy, VEGFR-2. Â